Effect of cellulose fiber from sorghum bagasse on the mechanical properties and biodegradability of polylactic acid - Yulianto; Dwini Normayulisa Putri; Meka Saima Perdani; Rita Arbianti; Lisman Suryanegara; Heri Hermansyah (Energy Reports, 2020)
Synthesis of biocomposites using polylactic acid (PLA) as the matrix and cellulose fiber from sorghum bagasse as the reinforcement agent has been carried out in this study. The objective was to improve the mechanical properties and biodegradability of PLA. In this study, cellulose fiber has been extracted from sorghum bagasse. Micro and nano-sized cellulose fiber was then produced by hydrolysis using sulfuric acid. Biocomposite was then made by casting film method using acetone as the solvent. Based on mechanical test, nanocellulose fiber gives better results on mechanical properties. Moreover, the tensile modulus and biodegradability of PLA were increase with the increasing of nanocellulose fiber concentration. Based on results, the addition of 2.5% nanocellulose fiber, improved the maximum strain from 5.19% to 11.59%. Otherwise, the best biodegradability of biocomposite was achieved on the addition of 15% nanocellulose fiber.
Keywords: 330; Biocomposite; Nanocellulose; Polylactic acid; Sorghum bagasse